The Temporal Relationship Between Local School Closure and Increased Incidence of Pediatric Diabetic Ketoacidosis - McCluskey, Casey K.; Zee-Cheng, Janine E.; Klein, Margaret J.; Scanlon, Matthew C.; Rotta, Alexandre T.; Remy, Kenneth E.; Carroll, Christopher L.; Shein, Steven L. (Frontiers in Pediatrics, 2022)
ABSTRACT Importance: The incidence of pediatric diabetic ketoacidosis (DKA) increased early in the COVID-19 pandemic, but the relative contribution of behavioral changes and viral-related pathophysiology are unknown. Objective: To evaluate the relationship between school closure date and onset of increased DKA to help clarify the etiology of the increased incidence. Design: A multi-center, quality-controlled Pediatric Intensive Care Unit (PICU) database was used to identify the number of admissions to a participating PICU with DKA on each calendar day from 60 days before local school closure to 90 days after, and compared to baseline data from the same periods in 2018-2019. Interrupted time series and multiple linear regression analyses were used to identify admission rates that differed significantly between 2020 and baseline. Setting: Eighty-one PICUs in the United States Participants: Children ages 29 days to 17 years admitted to a PICU with DKA Exposures: Statewide school closure Main outcome/measure: Rate of admission to the PICU for DKA. Results: There were 1936 admissions for children with DKA in 2020 and 1795 admissions/year to those same PICUs in 2018-2019. Demographics and clinical outcomes did not differ before school closure, but pandemic-era patients were less often white and had longer hospital length of stay in the post-school closure period. The difference between 2020 admissions and 2018-2019 admissions was not different than zero before school closure, and significantly higher than zero after school closure, but was significantly increased in 2020 at >30 days after school closure (p = 0.039). Conclusions/Relevance: An increase in pediatric DKA admissions began one month after school closures. Given that behavioral changes started near school closure dates and viral activity peaked weeks after, this suggests that behavioral factors may not be the primary etiology and it is possible that SARS-CoV-2 infection may have direct effects on pediatric DKA.